1990
DOI: 10.1080/08964289.1990.9934608
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological and Psychological Effects of the Expression and Inhibition of Emotion

Abstract: Previous work has indicated that humor enhances immunity, but the immunological effects of overt crying have not been studied. Thirty-nine women viewed sad and humorous videotapes and either inhibited or expressed overt expressions of laughter and weeping; these were observed and timed. Moods and immunity (S-IgA) were repeatedly measured. The humorous stimulus resulted in improved immunity, regardless of the overt laughter expressed; overt crying was immunosuppressive, whereas the inhibition of weeping in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 17 publications
3
36
0
1
Order By: Relevance
“…Individuals who scored high on measures of sense of humor were found to be more responsive to comic material (Lefcourt et al, 1990), less responsive to comic material (Dillon et al, 1985), or responded the same way to comic material as individuals who scored low on sense of humor (Lefcourt et al, 1990). In addition, it is not clear if sense of humor is associated with higher levels of resting levels of s-IgA, since some authors found a positive relation (Dillon et al, 1985), while others reported no relation (Labott et al, 1990;Lefcourt et al, 1990). These contradictory findings may be due to the fact that the studies differed in several key variables, including the measures used to assess sense of humor, movies selected to elicit humor, and methods used to assay s-IgA.…”
Section: Discussionmentioning
confidence: 49%
“…Individuals who scored high on measures of sense of humor were found to be more responsive to comic material (Lefcourt et al, 1990), less responsive to comic material (Dillon et al, 1985), or responded the same way to comic material as individuals who scored low on sense of humor (Lefcourt et al, 1990). In addition, it is not clear if sense of humor is associated with higher levels of resting levels of s-IgA, since some authors found a positive relation (Dillon et al, 1985), while others reported no relation (Labott et al, 1990;Lefcourt et al, 1990). These contradictory findings may be due to the fact that the studies differed in several key variables, including the measures used to assess sense of humor, movies selected to elicit humor, and methods used to assay s-IgA.…”
Section: Discussionmentioning
confidence: 49%
“…Since then, some evidence indi-cates that laughter can ameliorate certain types of pain (e.g., Ref. [99]), may promote immune functions [43] and reduce some physiological and psychological stress responses [3,100], while enhancing feelings of well-being, in part by counteracting negative affects [41,93]. Some of these effects could be due to the release of endogenous opioids and oxytocin -neuropeptides that are known to be important in mediating social affect [16,34,55], but many other brain and body chemistries are likely to be involved [3].…”
Section: Clinical Implications Of This Work With a Focus On Adhd Addmentioning
confidence: 99%
“…In contrast, Stone et al [10] found that undesirable events that increased negative emotions were correlated with decreases in SIgA level. Labott et al [11] found that participants' SIgA concentrations decreased as they released their negative emotions by crying after watching a sad video. However, Martin et al [12] found no evidence for changes of SIgA if participants cried while watching a sad video.…”
mentioning
confidence: 98%